Halal Certification for Micro and Small Businesses in Bandar Lampung, Indonesia: An Evaluation from the Maslahah Perspective - Jayusman, Jayusman; Efrinaldi, Efrinaldi; Nurhayati, Agustina; Shafra, Shafra; Ningsih, Dwi Surya (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study examines the implementation of halal certification for Micro and Small Enterprises based on Article 79 of Government Regulation Number 39 of 2021 on the Administration of Halal Product Assurance (PP No. 39/2021). The implementation of this regulation in Labuhan Dalam Subdistrict, Tanjung Senang District, and Bandar Lampung City has not been carried out effectively because there are still Micro and Small Enterprise products that have not been halal certified. The focus of this study is: What is the maslahah review on the implementation of Article 79 of PP No. 39/2021 regarding halal certification for Micro and Small Enterprises in Labuhan Dalam Subdistrict, Tanjung Senang District, Bandar Lampung City? The method used is field research with qualitative descriptive analysis. The primary data sources are interview results and observations with micro and small business actors who are required to have halal certification in Labuhan Dalam Subdistrict, Tanjung Senang District, Bandar Lampung City, and BPJPH employees of the Lampung Provincial Office of the Ministry of Religion in the Halal Task Force. The conclusion of the study is that, from the maslahah perspective, Article 79 of PP No. 39/2021 has not been well implemented in Labuhan Dalam. This is because the government, BPJPH, has not fully carried out its duties to execute its tasks and authorities to provide information, education, and socialization related to the obligation to have halal certification to micro and small business actors, as well as the lack of awareness of micro and small business actors regarding the obligation to have a halal certificate. This naturally brings harm to micro- and small-scale businesses and the community.